Rescue of protein expression defects may not be enough to abolish the pro‐arrhythmic phenotype of long QT type 2 mutations. (27th May 2016) - Perry, Matthew D.; Ng, Chai Ann; Phan, Kevin; David, Erikka; Steer, Kieran; Hunter, Mark J.; Mann, Stefan A.; Imtiaz, Mohammad; Hill, Adam P.; Ke, Ying; Vandenberg, Jamie I.
Abstract : Key points: Most missense long QT syndrome type 2 (LQTS2) mutations result in Kv11.1 channels that show reduced levels of membrane expression. Pharmacological chaperones that rescue mutant channel expression could have therapeutic potential to reduce the risk of LQTS2‐associated arrhythmias and sudden cardiac death, but only if the mutant Kv11.1 channels function normally (i.e. like WT channels) after membrane expression is restored. Fewer than half of mutant channels exhibit relatively normal function after rescue by low temperature. The remaining rescued missense mutant Kv11.1 channels have perturbed gating and/or ion selectivity characteristics. Co‐expression of WT subunits with gating defective missense mutations ameliorates but does not eliminate the functional abnormalities observed for most mutant channels. For patients with mutations that affect gating in addition to expression, it may be necessary to use a combination therapy to restore both normal function and normal expression of the channel protein. Abstract: In the heart, Kv11.1 channels pass the rapid delayed rectifier current ( I Kr ) which plays critical roles in repolarization of the cardiac action potential and in the suppression of arrhythmias caused by premature stimuli. Over 500 inherited mutations in Kv11.1 are known to cause long QT syndrome type 2 (LQTS2), a cardiac electrical disorder associated with an increased risk of life threatening arrhythmias. Most missense mutations in Kv11.1 reduce the amount of channel protein expressed at the membrane and, as a consequence, there has been considerable interest in developing pharmacological agents to rescue the expression of these channels. However, pharmacological chaperones will only have clinical utility if the mutant Kv11.1 channels function normally after membrane expression is restored. The aim of this study was to characterize the gating phenotype for a subset of LQTS2 mutations to assess what proportion of mutations may be suitable for rescue. As an initial screen we used reduced temperature to rescue expression defects of mutant channels expressed in Xenopus laevis oocytes. Over half (∼56%) of Kv11.1 mutants exhibited functional gating defects that either dramatically reduced the amount of current contributing to cardiac action potential repolarization and/or reduced the amount of protective current elicited in response to premature depolarizations. Our data demonstrate that if pharmacological rescue of protein expression defects is going to have clinical utility in the treatment of LQTS2 then it will be important to assess the gating phenotype of LQTS2 mutations before attempting rescue. Key points: Most missense long QT syndrome type 2 (LQTS2) mutations result in Kv11.1 channels that show reduced levels of membrane expression. Pharmacological chaperones that rescue mutant channel expression could have therapeutic potential to reduce the risk of LQTS2‐associated arrhythmias and sudden cardiac death, but only if the mutant Kv11.1 channels function normally (i.e. like WT channels) after membrane expression is restored. Fewer than half of mutant channels exhibit relatively normal function after rescue by low temperature. The remaining rescued missense mutant Kv11.1 channels have perturbed gating and/or ion selectivity characteristics. Co‐expression of WT subunits with gating defective missense mutations ameliorates but does not eliminate the functional abnormalities observed for most mutant channels. For patients with mutations that affect gating in addition to expression, it may be necessary to use a combination therapy to restore both normal function and normal expression of the channel protein.